Moderate systemic therapeutic hypothermia is insufficient to protect blood-spinal cord barrier in spinal cord injury - Zhou, Rubing; Li, Junzhao; Wang, Ruideng; Chen, Zhengyang; Zhou, Fang (Frontiers in Neurology, 2022)
Blood–spinal cord barrier (BSCB) disruption is a pivotal event in spinal cord injury (SCI) that aggravates secondary injury but has no specific treatment. Previous reports have shown that systemic therapeutic hypothermia (TH) can protect the blood–brain barrier after brain injury. To verify whether a similar effect exists on the BSCB after SCI, moderate systemic TH at 32°C was induced for 4 h on the mice with contusion-SCI. In vivo two-photon microscopy was utilized to dynamically monitor the BSCB leakage 1 h after SCI, combined with immunohistochemistry to detect BSCB leakage at 1 and 4 h after SCI. The BSCB leakage was not different between the normothermia (NT) and TH groups at both the in vivo and postmortem levels. The expression of endothelial tight junctions was not significantly different between the NT and TH groups 4 h after SCI, as detected by capillary western blotting. The structural damage of the BSCB was examined with immunofluorescence, but the occurrence of junctional gaps was not changed by TH 4 h after SCI. Our results have shown that moderate systemic TH induced for 4 h does not have a protective effect on the disrupted BSCB in early SCI. This treatment method has a low value and is not recommended for BSCB disruption therapy in early SCI.